Pinkalicious and aqua, the mini-mermaid ebook - Kann, Victoria (Pinkalicious., 2021)
Pinkalicious + Peter + mermaids makes for a charming and fun book for little ones. Aqua, the mini-mermaid, shares her special places with Pinkalicious and Peter, including a cove filled with sparkling sea glass and rainbow-colored shells. The friends are worried, though, when they see fins approaching. Fortunately, the fins don't belong to sharks. It's a pair of dolphins. Pink, of course! Plus don't miss Pinkalicious & Peterrific on PBS Kids!